Purification and molecular properties of malate dehydrogenase from the marine diatom Nitzschia alba. - Yueh, A Y (1989)
Malate dehydrogenase (EC 1.1.1.37) was purified to homogeneity from the marine diatom Nitzschia alba. The purification steps consisted of (NH4)2SO4 precipitation, ion-exchange chromatography, Blue Sepharose affinity chromatography and gel filtration. A typical procedure provided 685-fold purification with 58% yield. The Mr of the holoenzyme was estimated to be 322,000 by gel filtration and 316,000 by ultracentrifugation. The enzyme migrated as a single polypeptide spot on two-dimensional polyacrylamide-gel electrophoresis with an Mr of 38,500, suggesting that the holoenzyme consists of eight identical subunits. This is the first case where malate dehydrogenase has been shown to be a homo-octamer; malate dehydrogenases from other sources are predominantly homodimers, with two homotetramers reported so far. The amino acid composition of the enzyme was determined and the N-terminal sequence of the subunit polypeptide was found to be Arg-Lys-Val-Ala-Val-Met-Gly-Ala-Ala-Gly-Gly-Ile-Gly-Gln-Pro-Leu-Ser-Leu- Leu-Leu - Lys-Leu-Ser-Pro-Gln-Val-Thr-Glu-Leu-Ser-Lys-Tyr-. For the first 21 amino acid residues, near-identical sequences were reported for the enzymes isolated from pig heart, Escherichia coli, yeast and watermelon. Other physicochemical and catalytic properties, such as sedimentation coefficient, partial specific volume, Stokes radius, excitation and emission maxima, Michaelis constants, pH optima, pH stability range and activation energy, of this enzyme are also presented.